The role of gender in providing expert advice on cyber conflict and artificial intelligence for military personnel - Fisher, Kelly (Frontiers in Big Data, 2022)
This article draws upon original qualitative interview data with Norwegian male and female cyberengineer cadets at the Norwegian Cyber Defense Academy, who could in the future be working with AI-enabled systems in a variety of positions throughout the Norwegian military, including supporting cyber in field operations, as well as cyber operations. The interviews explored how these cadets feel they as cyberengineers will be perceived in their future positions in the military, what challenges they feel they may face as cyberengineers, and how gender may play a role in this. Many of the cyberengineers expressed concern about being able to communicate cyber to their non-technology specialist colleagues and commanding officers due to the increasing complexity of new technologies, and felt that soldiers who are non-technology specialists have minimal understanding of what is ongoing in the cyber domain. However, female interviewees expressed specific concerns that they feel as women, that they do not fit the stereotype of who is a cyberengineer or who is seen as technologically competent, and that this has implications for how they feel others perceive their competence levels. The findings from this article highlight the need for military institutions to focus on developing communication skills among those working with cyber and take into consideration gender. As the role of cyber is expected to grow in military operations, cyberengineers will need to find ways of communicating effectively with non-specialists – especially as complex AI-enabled systems are introduced.